ألفاظ "الأمة" ومشتقاتها في القرآن الكريم :‏ ‏دراسة صرفية دلالية /‏ - حاج بسر، ماريسا
This linguistic study examines a group of Qur´anic wordings, and aims to analyze the words of Ummah inductively and morphologically. To achieve these objectives, the study used two approaches: descriptive approach and analytical approach, the study also used the interpretation of Qur´anic books, dictionaries and morphology books to determine the origin of the term Ummah. In the analytical approach, the study extracted the connotations of the term Ummah and its derivatives from the interpretations of commentators such as Ibn Nashir, al-Razi, Ibn Qutaybah, al-Shawkani and others of these Qur´anic verses. The study concludes that there are many connotations of the term Ummah, including the significance of time, the significance of a good teacher, group of animals and birds, way of life, varieties, and so on. All these meanings refer to differences of opinion among the commentators in the interpretation of this term in the Qur´anic context.